Effect of nebulized dexmedetomidine on gag reflex suppression and sedation quality in pediatric patients undergoing gastrointestinal endoscopy: a randomized controlled trial - Esra Turunc; Yasemin Burcu Ustun; Sezgin Bilgin; Cengiz Kaya; Ersin Koksal; Burhan Dost (BMC Anesthesiology)
Abstract Background Pediatric patients undergoing upper gastrointestinal (GI) interventions frequently require sedation and analgesia due to the challenges associated with endoscopic probe placement, particularly the gag reflex. This study investigates the effects of nebulized dexmedetomidine as a premedication on the gag reflex in pediatric patients undergoing gastrointestinal endoscopy. Methods We conducted a single-center, prospective, randomized controlled trial at the Pediatric Gastroenterology Clinic of Ondokuz Mayis University School of Medicine from January to April 2024. Participants aged 2–17 years scheduled for upper GI endoscopy were randomized to receive nebulized dexmedetomidine (2 µg /kg) or no premedication. The primary outcome measured was the severity of the gag reflex during the procedure. Secondary outcomes included cough incidence, separation anxiety, postoperative agitation, and endoscopist satisfaction. Statistical analyses were performed with significance set at p < 0.050. Results A total of 120 patients were analyzed. The dexmedetomidine group demonstrated a significantly lower incidence of gag reflex (88.3% with no gag reflex vs. 30% in the control group, p < 0.001) and coughing (95% vs. 55%, p < 0.001). Separation anxiety scores were also significantly lower in the dexmedetomidine group (p < 0.005). Additionally, the need for additional anesthetics was reduced, and endoscopist satisfaction was significantly higher. No significant differences in complications were observed between the two groups (p = 0.600). Conclusions Nebulized dexmedetomidine is a safe and effective premedication for pediatric patients undergoing endoscopic procedures, significantly reducing gag and cough reflexes, decreasing anesthetic requirements, and enhancing endoscopist satisfaction. This approach improves the comfort and safety of pediatric endoscopy procedures. Trials registration ClinicalTrials.gov: NCT06218797, date of registration 27/12/2023.